2008
DOI: 10.4039/n07-058
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of cavity-nesting bees (Hymenoptera: Apoidea) within apple orchards and wild habitats in the Annapolis Valley, Nova Scotia, Canada

Abstract: Abstract-Solitary cavity-nesting bees, especially trap-nesting Megachilidae, have great potential as commercial pollinators. A few species have been developed for crop pollination, but the diversity, abundance, and potential pollination contributions of native cavity-nesting bees within agricultural systems have seldom been assessed. Our objectives were to compare the diversity and fecundity of cavity-nesting bees in Nova Scotia in natural ecosystems with those in apple orchards under three levels of managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 27 publications
3
73
0
Order By: Relevance
“…A likely explanation is that although the amount of pollen provided by the apple orchard is ample enough, the timing of blossom of surrounding fruit trees such as cherry, pear, and red currant extended the provision of pollen to a longer time period. In accordance with this, Sheffield et al (2008) report a greater reproductive success in Osmia lignaria, when additional pollen is supplied by planting lupine in the vicinity (less than 600 m) of orchards. Food availability has also been demonstrated to correlate positively at the landscape scale for bumblebees (Westphal et al 2003;Williams and Kremen 2007) and for O. lignaria (Williams and Kremen 2007) and in caging experiments with Osmia pumilla (Goodell 2003).…”
Section: Abundancesupporting
confidence: 71%
See 1 more Smart Citation
“…A likely explanation is that although the amount of pollen provided by the apple orchard is ample enough, the timing of blossom of surrounding fruit trees such as cherry, pear, and red currant extended the provision of pollen to a longer time period. In accordance with this, Sheffield et al (2008) report a greater reproductive success in Osmia lignaria, when additional pollen is supplied by planting lupine in the vicinity (less than 600 m) of orchards. Food availability has also been demonstrated to correlate positively at the landscape scale for bumblebees (Westphal et al 2003;Williams and Kremen 2007) and for O. lignaria (Williams and Kremen 2007) and in caging experiments with Osmia pumilla (Goodell 2003).…”
Section: Abundancesupporting
confidence: 71%
“…Nevertheless, as this is a field experiment and we have no control site established, we cannot rule out that the increase is also partly because of beneficial effects such as good weather conditions, but given the magnitude of the effect, the limiting effect of nesting opportunities (cf. Sheffield et al 2008;SteffanDewenter and Schiele 2008) for this species could be demonstrated. An important contribution to this increase is probably the fact that due to opening of the bamboo canes, we separated infested and undeveloped cocoons from the healthy ones, which kept the otherwise likely increase of the parasite population under control.…”
Section: Population Sizementioning
confidence: 75%
“…Much is known about the biology of many leafcutter bees due to their importance in crop pollination (Hobbs & Lilly 1954;Pengelly 1955;Osgood 1974;Peterson et al 1992;Richards 1993;Raw 2002) and the fact that many species accept trap-nests (Medler 1959(Medler , 1964Fye 1965;Krombein 1967;Frolich & Parker 1983;O'Toole & Raw 1991;Sheffield et al 2008). Most species nest above ground in pre-existing cavities (Figure B) or excavate into pithy stems or decomposing wood (Stephen 1956;Ivanochko 1979).…”
Section: Biology Of Megachilementioning
confidence: 99%
“…Many of the species of Megachile that nest in pre-existing cavities will utilize artificial nesting substrates (e.g., Fye, 1965;Krombein, 1967;Stephen & Every, 1970;Sheffield et al, 2008, MacIvor & Packer, 2015MacIvor, in press), popularly called bee condos or hotels (e.g., Ravoet et al, 2014;MacIvor & Packer, 2015;Fortel et al, 2016), or trap/cavity nests (e.g., Krombein, 1967;O'Neil & O'Neil, 2016;MacIvor, in press). In these artificial nesting sites, the nesting cavities are typically pre-constructed to run horizontally and perpendicular to the nest front surface, though this arrangement may not always be available in natural cavities.…”
mentioning
confidence: 99%
“…In these artificial nesting sites, the nesting cavities are typically pre-constructed to run horizontally and perpendicular to the nest front surface, though this arrangement may not always be available in natural cavities. The diameter of the individual tunnels can vary to support occupant diversity (e.g., Tscharntke et al, 1998;Sheffield et al, 2008), and influence sex-ratio for target species (e.g., Stephen & Osgood, 1965).…”
mentioning
confidence: 99%